How do we express nonics in terms of the monic?

Algebra Level 4

Given that r r is a real number satisfying r + 1 r = 3 r + \dfrac1r = 3 , find the value of r 9 + 1 r 9 r^9+ \dfrac1{r^9} .


The answer is 5778.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

I'll be repeatedly using the fact that if a + b + c = 0 a+b+c=0 ,then a 3 + b 3 + c 3 = 3 a b c a^3+b^3+c^3=3abc .

Here we go: r + 1 r + ( 3 ) = 0 r 3 + 1 r 3 27 = 9 r 3 + 1 r 3 + ( 18 ) = 0 r 9 + 1 r 9 5832 = 54 r 9 + 1 r 9 = 5778 \begin{aligned} r+\frac{1}{r}+(-3)&=0\\ \implies r^3+\frac{1}{r^3}-27&=-9\\ r^3+\frac{1}{r^3}+(-18)&=0\\ \implies r^9+\frac{1}{r^9}-5832&=-54\\ \implies r^9+\frac{1}{r^9}&=\boxed{5778} \end{aligned}

Thats unique!

Harsh Shrivastava - 5 years ago

r 3 + 1 r 3 = ( r + 1 r ) 3 ( 3 × r × 1 r × ( r + 1 r ) ) = 3 3 3 ( 3 ) = 18 r^3+ \dfrac 1 {r^3}=\left(r+\dfrac 1 r \right)^3-\left(3 \times r \times \dfrac 1 r \times \left(r+ \dfrac 1 r \right)\right)=3^3-3(3)=18 .

Similarly, r 9 + 1 r 9 = ( r 3 + 1 r 3 ) 3 ( 3 × r 3 × 1 r 3 × ( r 3 + 1 r 3 ) ) = 1 8 3 3 ( 18 ) = 5778 r^9+\dfrac 1 {r^9}=\left(r^3+\dfrac 1 {r^3}\right)^3-\left(3 \times r^3 \times \dfrac 1 {r^3} \times \left(r^3+\dfrac 1 {r^3}\right)\right)=18^3-3(18)=\boxed{5778} .

Nicely done. +1

Sharky Kesa - 5 years ago

Here's another way, let r = e i θ r=e^{i\theta} where θ \theta is a complex number.

Note that e i x = cos x + i sin x x C e^{ix}=\cos x+ i\sin x \quad \forall x \in \mathbb{C}

Then, we're given that 2 cos θ = 3 2\cos \theta = 3 and we need to find 2 cos 9 θ 2\cos 9\theta . Using triple angle formulae (which is valid for complex arguements) twice, we get 2 cos 9 θ = 5778 2 \cos 9\theta =\boxed{5778}

I love this solution! Very easy and neat.

Raz Lerman - 5 years ago
Chew-Seong Cheong
May 24, 2016

r + 1 r = 3 ( r + 1 r ) 3 = 3 3 r 3 + 3 r + 3 r + 1 r 3 = 27 r 3 + 1 r 3 = 27 3 ( r + 1 r ) = 27 9 = 18 \begin{aligned} r + \frac{1}{r} & = 3 \\ \left(r + \frac{1}{r}\right)^3 & = 3^3 \\ r^3+3r+\frac{3}{r}+\frac{1}{r^3} & = 27 \\ \implies r^3 + \frac{1}{r^3} & = 27 - 3 \left(r + \frac{1}{r}\right) \\ & = 27 - 9 = 18 \end{aligned}

( r 3 + 1 r 3 ) 3 = 1 8 3 r 9 + 3 r 3 + 3 r 3 + 1 r 9 = 5832 r 9 + 1 r 9 = 5832 3 ( r 3 + 1 r 3 ) = 5832 54 = 5778 \begin{aligned} \left(r^3 + \frac{1}{r^3}\right)^3 & = 18^3 \\ r^9+3r^3+\frac{3}{r^3}+\frac{1}{r^9} & = 5832 \\ \implies r^9 + \frac{1}{r^9} & = 5832 - 3 \left(r^3 + \frac{1}{r^3}\right) \\ & = 5832 - 54 = \boxed{5778} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...